THE INFLUENCE OF E-WORD OF MOUTH AND E-COMMERCE ON CONSUMER DECISIONS IN CHOOSING THE INDRIVE ONLINE TRANSPORTATION APPLICATION (CASE STUDY OF MARINDAL I, PATUMBAK I DISTRICT) - Michael Gho; Dedy Lazuardi; Ihdina Gustina (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
The development and progress of information technology has now penetrated the field of transportation to facilitate human activities. With the increasing need for fast and easy transportation, online transportation service businesses using applications have emerged. The use of technology in the transportation sector provides convenience in ordering, time and cost efficiency, making it a distinct advantage for online transportation service providers compared to conventional transportation. InDrive is a ridesharing application platform (online transportation service provider) which is similar to Grab and Gojek, this application allows users to order cars/motorbikes at prices that can be negotiated between the driver and passenger. This research was conducted to determine and measure the influence of E-Word of Mouth and E-Commerce on the Decision to Choose the Indrive Online Transportation Application with a case study of Marindal I, Patumbak I District. This research uses a quantitative approach by determining a judgment sampling sample with criteria where the customer is age productive work using the indrive application which was used as a research sample. Using the Slovin sampling technique with a confidence level of 90% and an error rate of 10%, the sample used in this research was 100 people. Proving the hypothesis in this research is assisted by using the SPSS version 25 application. The results of this research are that the E-Word of Mouth variable partially has a positive and significant effect on the decision to choose Indrive online transportation. Partially, the E-Commerce variable has a positive and significant effect on the decision to choose Indrive online transportation. Simultaneously, E-Word of Mouth and E-Commerce have a positive and significant influence on the decision to choose Indrive online transportation. And 60.5% of voting decisions are influenced by E-Word of Mouth and E-Commerce.